Computer Testing as a Method of Controlling Professional Foreign Language Competence - Пономарьова, О. І.; Ковальова, А. В. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2015)
Global information processes and social economic changes in Ukrainetrigger educational reforming in the country. Information technologies (IT) open new perspectives for foreign languages teaching at higher educational establishments. The aim of the article is to consider the didactic peculiarities of computer testing and possibilities of its practical application in the process of training foreign language for special purposes as a means of students’ knowledge control. The authors analyze the history of computer testing that can be divided into three periods: structural, communicative and integrative.Complex software classification according to the methodological objectives (control, training, demonstrating, informing programs, etc.) is given in the article. The authors emphasize, that computer assessment, using unique abilities of a computer to select, group instantly and save any block of information, enables teachers to give individual recommendations to the students, grade the tasks and results and help students to understand the mistakes.The authors give principles of computer testing professional foreign language competence which should be taken into account while composing tests (validity, complexity, differentiation, reliability, shortness, practical value, etc.). They examine the functions of computer testing (directing, motivating, orienting, training, evaluating, correlating, educating and predicting). To sum up, it can be concluded that computer testing today as an essential method of controlling professional foreign language competence should be used within the system of traditional assessment methods because it is an optimal evaluating indicator of the students’ language learning progress and readiness for professional activity.